Improved Regional Homogeneity in Chronic Insomnia Disorder After Amygdala-Based Real-Time fMRI Neurofeedback Training - Li, Zhonglin; Liu, Jiao; Chen, Bairu; Wu, Xiaoling; Zou, Zhi; Gao, Hui; Wang, Caiyun; Zhou, Jing; Qi, Fei; Zhang, Miao; He, Junya; Qi, Xin; et al. (Frontiers in Psychiatry, 2022)
Background: Chronic insomnia disorder (CID) is a highly prevalent sleep disorder, which influence people’s daily life and is even life threatening. However, whether the resting-state regional homogeneity (ReHo) of disrupted brain regions in CID can be reshaped to normal after treatment remains unclear. Methods: A novel intervention-real-time fMRI neurofeedback (rtfMRI-NF) was used to train 28 CID patients to regulate the activity of left amygdala for three sessions in six weeks. The ReHo methodology was adopted to explore its role on resting-state fMRI data, which were collected before and after training. Moreover, the relationships between changes of clinical variables and ReHo value of altered regions were determined. Results: Results showed that the bilateral dorsal medial prefrontal cortex, supplementary motor area (SMA), and left dorsal lateral prefrontal cortex had decreased ReHo values, whereas the bilateral cerebellum anterior lobe (CAL) had increased ReHo values after training. Some clinical scores markedly decreased, including Pittsburgh sleep quality index, insomnia severity index, Beck depression inventory, and Hamilton anxiety scale (HAMA). Additionally, the ReHo values of the left CAL was positively correlated with the change in Hamilton depression scale score, and a remarkable positive correlation was found between the ReHo values of the right SMA and the HAMA score. Conclusions: Our study provided an objective evidence that amygdala-based rtfMRI-NF training could reshape abnormal ReHo and improve sleep in patients with CID. The improved ReHo in CID provide insights into the neurobiological mechanism for the effectiveness of this intervention. However, larger double-blinded sham-controlled trials are needed to confirm our results from this initial study.